Synchronizing Oscillatory Chaos in the Brain - Diaz-Munoz, H (Elsevier B.V., 2019)
We constructed the idea of oscillatory chaos in the brain during the process to use a non-linear estimator that allows us to have a more global, emergent and integrated view of the brain dynamics in its unpredictable realm of quasi-chaos forces. Through extend the application of the Hurst exponent as an estimator of the chaos/order balance of a time series, we explore such oscillatory dynamic of the brain at various time scales, applying at the end a recursive Hurst exponent estimator over a time series built from a time series of 1 second H chaos estimators. Results suggest the appearance of an emergent meta-chaos (HH) envelope that could be implied in provide order and direction in a multi-fractal chaotic system as the brain, as far as these HH estimators values resulted influenced by the Hurst persistent effect (H>0.5). This meta-chaos estimator is sensitive to intra- and inter-individual differences, symmetric/asymmetric intra-individual patterns, and also to the frequency range of the EEG signal studied. © 2020 The Authors. Published by Elsevier B.V.